The Factors and Pathways Regulating the Activation of Mammalian Primordial Follicles in vivo - Chen, Yao; Yang, Weina; Shi, Xu; Zhang, Chenlu; Song, Ge; Huang, Donghui (Frontiers in Cell and Developmental Biology, 2020)
Mammalian ovaries consist of follicles as basic functional units, each follicle is comprised of an innermost oocyte and several surrounding flattened granulosa cells. Unlike males, according to the initial size of primordial follicle pool and the rate of its activation and depletion, a female’s reproductive life has been determined early in life. Primordial follicles, once activated, will get into an irreversible process of development. Most follicles undergo atretic degeneration and only a few of them could mature and ovulate. Although there are lots of researches contributing to exploring the activation of primordial follicles, little is known about its underlying mechanisms. Thus, in this review, we collected the latest papers and summarized signaling pathways as well as some factors involved in the activation of primordial follicles, hoping to lead to a more profound understanding of the cellular and molecular mechanisms of primordial follicle activation.